PEMENUHAN KEBUTUHAN GIZI BALITA KELUARGA PETANI - Kurniyawan, Enggal Hadi; Nurul Firdaus, Azzahra Ganandya; Sari, Firli Riana; Putri, Melsanda Holipin; Diyanti, Sister Putri; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad (JOURNAL HEALTH AND NUTRITIONS, 2024)
The problem of fulfilling toddler nutrition is still a concern to farming families. The issue of meeting nutritional needs is always synonymous with poverty and parents educational level. Several factors affect toddler nutrition including socio-economic, diet, lack of environmental sanitation, and household food security. Therefore, this analysis aims to determine the factors associated with increasing the fulfillment of toddler nutrition in farming families. The study used the literature review method to obtain as many as ten journals to be analyzed after selection through inclusion and exclusion criteria. The article search strategy uses databases on international journal sites such as google scholar and science direct. Results od study indicated the increament of nutritional fulfillment for toddlers in farming families is influenced by several factors such as employment status, level of education or knowledge, types of communication that affect on children diet, parenting style, number of family members, and household food security in farming families. Conclusions of the study that  status of occupation, level of education or knowledge, type of communication, parenting style, number of family members, and household food security affect the fulfillment of the nutritional needs of toddlers, so particular interventions are needed to help increase the fulfillment of the dietary needs of toddlers such as support for housewives, family planning, and education about giving eating and child nutrition, how to communicate in strategies for providing proper food and training on how to make healthy food with local ingredients.Permasalahan pemenuhan gizi balita masih menjadi perhatian keluarga petani. Persoalan pemenuhan kebutuhan gizi selalu identik dengan kemiskinan dan tingkat pendidikan orang tua. Beberapa faktor yang mempengaruhi gizi balita diantaranya sosial ekonomi, pola makan, sanitasi lingkungan yang kurang, dan ketahanan pangan rumah tangga. Oleh karena itu analisis ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan peningkatan pemenuhan gizi balita pada keluarga petani. Metode penelitian menggunakan metode literatur review sehingga diperoleh sebanyak sepuluh jurnal untuk dianalisis setelah diseleksi melalui kriteria inklusi dan eksklusi. Strategi pencarian artikel menggunakan database pada situs jurnal internasional seperti google scholar dan science direct. Hasil penelitian menunjukkan peningkatan pemenuhan gizi balita pada keluarga petani dipengaruhi oleh beberapa faktor seperti status pekerjaan, tingkat pendidikan atau pengetahuan, jenis komunikasi yang mempengaruhi pola makan anak, gaya pengasuhan, jumlah anggota keluarga, dan ketahanan pangan rumah tangga pada keluarga petani. Kesimpulan penelitian adalah status pekerjaan, tingkat pendidikan atau pengetahuan, jenis komunikasi, pola asuh orang tua, jumlah anggota keluarga, dan ketahanan pangan rumah tangga berpengaruh terhadap pemenuhan kebutuhan gizi balita, sehingga diperlukan intervensi khusus untuk membantu meningkatkan pemenuhan kebutuhan gizi balita. Kebutuhan gizi balita seperti dukungan kepada ibu rumah tangga, keluarga berencana, dan edukasi tentang pemberian makan dan gizi anak, cara mengkomunikasikan strategi penyediaan makanan yang benar dan pelatihan cara membuat makanan sehat dengan bahan lokal.